Effect of Parental Income Level and Parental Education Level on the Interest of Prospective Students to Continue Studying in Higher Education - Dindin Abidin; Pandu Adi Cakranegara; Eka Budi Yulianti; Irmah Halimah Bachtiar; Muhammad Alda Wijayanto (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this research is to analyze effect of parental income level and parental education level on the interest of prospective students to continue studying in Higher Education. This type of research in this study uses quantitative research. Population in this study are Senior High School Students in Medan City in 2021. Sample is taken randomly using snowball sampling technique. So sample in this study are 100 Senior High School Students in Medan City. Data analysis using multiple linear regression analysis. The results of the study show that parental income level has a significant effect on the interest of prospective students to continue studying in Higher Education. Parental education level has a significant effect on the interest of prospective students to continue studying in Higher Education.